Innovation Through the Titip Bandaku Program at Library and Archives Services of Klaten Regency, Indonesia - Puspitasari, Diana Ayu; Ikram, Nabil (Department Library of Governance Institut of Home Affairs, 2024)
Background: Concerning archival services, local government agencies are responsible for managing archives within the regions. The Klaten Regency Government has adopted technology to produce innovation in public archives services, focusing on the management and preservation of archival records. To achieve this objective, the Titip Bandaku (Titip Berkas Arsip Digitalku) archival innovation program was established, facilitating the digital conversion of physical documents. However, in the implementation of program which has been running for approximately 5 years, the volume of digitized documents has not met the targets set by Library and Archives Services as the implementing government agency. Purpose: Therefore, This study aimed to examine the implementation of the Titip Bandaku program in protecting and preserving archives, identifying the obstacles included, and how the Klaten Regency Library and Archives Services addressed these challenges. Method: A qualitative-descriptive method was used to describe the implementation of the Titip Bandaku innovation based on the theory of innovation (State Administration Institute, 2017) with two dimensions of innovation namely output and outcome5. Data collection methods included observation, interviews, and documentation. The collected data further underwent stages of analysis through data collection, reduction, presentation, and conclusion. Result: The implementation of the Titip Bandaku Innovation Program positively impacted the preservation of community archives against disasters by digitizing records. On the Output indicator, program was a pioneering effort within Klaten Regency to protect archives in disaster-prone areas, offering swift and customized services despite capacity limitations. On the Outcome indicator, program improves the security of community archives, lowers transportation costs through a mobile services system, and shows sustainability with the backing of regulations, funding, and continuous enhancement of facilities and services. Conclusion: The Titip Bandaku program at the Klaten Regency Library and Archives Services did not achieve optimal functionality. Factors hindering progress included limited human resources, inadequate facilities and infrastructure, and the poor condition of some archives. To improve program’s effectiveness, several measures were recommended, such as forming a dedicated Titip Bandaku team, increasing public outreach through community activities, and fostering partnerships with relevant stakeholders.